2002
DOI: 10.1007/s706-002-8247-7
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Treatment of 5-(6-methyl-2,4-dioxo-1,2,3,4-tetrahydro-3-pyrimidinyl)-methyl-1,3,4oxadiazole-2-thione with haloalkanes yielded oxadiazole S-alkyl derivatives, whereas its reaction with formaldehyde and amines resulted in formation of oxadiazole N(3)-aminomethyl derivatives. The alkylation of 2-alkylsulfanyl-5-(6-methyl-2,4-dioxo-1,2,3,4-tetrahydro-3-pyrimidinyl)-methyl-1,3,4-oxadiazoles with methyl bromoacetate proceeded at the N(1)-position of pyrimidine to give 2-alkylsulfanyl-5-(1-methoxycarbonylmethyl-6-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Because of our particular interest in the synthesis and investigation of pyrimidines with five-membered heterocyclic substituents [24,[26][27][28], such as thiadiazoles, oxadiazoles, and triazoles in the side chain, we successfully synthesized aminotriazolethiones 2 o-u from the corresponding esters by employing the synthetic method described here. Yields of the mentioned compounds 2 o-v varied from 39% to 59%.…”
Section: Methodsmentioning
confidence: 99%
“…Because of our particular interest in the synthesis and investigation of pyrimidines with five-membered heterocyclic substituents [24,[26][27][28], such as thiadiazoles, oxadiazoles, and triazoles in the side chain, we successfully synthesized aminotriazolethiones 2 o-u from the corresponding esters by employing the synthetic method described here. Yields of the mentioned compounds 2 o-v varied from 39% to 59%.…”
Section: Methodsmentioning
confidence: 99%
“…For background to the use of 1,3,4-oxadiazoles, see: Erden et al (2005); Smicius et al (2002); Dutta & Kataky (1992). For details of the biological activity of 1,3,4-oxadiazoles, see : Chen, et al (2000); Mehuskiene, et al (2003); El-Emam et al (2004); Krasovshii et al (2000).…”
Section: Related Literaturementioning
confidence: 99%
“…(Erden et al, 2005, Smicius et al, 2002, Dutta & Kataky, 1992 and their wide range of biological activities, such as bactericidal, anti-inflammatory, antiviral, antimicrobial, tuberculostatic, anti convulsive and fungicidal activities (Chen et al, 2000;Mehuskiene et al, 2003;El-Emam et al, 2004;Krasovshii et al, 2000). The title compound was prepared by refluxing 3,4,5-trimethoxybenzohydrazide and potassium hydroxide with carbon disulfide in ethanol.…”
Section: D-hámentioning
confidence: 99%
“…Recent studies have shown that some compounds can be used as corrosion inhibitors of steal [21, 22], and some can be used as semiconductors [23], and others used in the metal complexes [24–36]. On the other hand, the cyclized products were also intensively studied because of their biological and other properties [37–40].…”
Section: Introductionmentioning
confidence: 99%
“…Thiosemicarbazides are versatile compounds, which have been extensively used in the synthesis of different heterocyclic ring systems [37–40]. Several authors developed a new simple and efficient procedure for preparation of thiosemicarbazide derivatives [32, 40].…”
Section: Introductionmentioning
confidence: 99%